THE IMPORTANCE OF USING DIALOGUES FOR ENHANCING SPEAKING SKILL OF YOUNG LEARNER - Abdulxayeva Gulginabonu; Igamberdieva Shahnoza (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
English is an international language; it is important for us to develop our speaking abilities as foreign students. The development of learners’ speaking abilities involves a variety of tactics. Teachers should work closely with students to help them develop their confidence so they can speak English with no reservations. In order to complete this duty, teachers hold a range of seminars and interviews in which each student takes part on their own and learns a great deal.